2019
DOI: 10.1002/adts.201900135
|View full text |Cite
|
Sign up to set email alerts
|

Design, Parameterization, and Implementation of Atomic Force Fields for Adsorption in Nanoporous Materials

Abstract: Molecular simulations are an excellent tool to study adsorption and diffusion in nanoporous materials. Examples of nanoporous materials are zeolites, carbon nanotubes, clays, metal-organic frameworks (MOFs), covalent organic frameworks (COFs) and zeolitic imidazolate frameworks (ZIFs). The molecular confinement these materials offer has been exploited in adsorption and catalysis for almost 50 years. Molecular simulations have provided understanding of the underlying shape selectivity, and adsorption and diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 531 publications
(823 reference statements)
2
55
0
Order By: Relevance
“…Figure 7 shows that self-diffusion coefficients calculated with the modified one-site model correlate the best with experimental QENS measurements. This modified force field performed poorly in predicting H 2 adsorption isotherms, cautioning the reader that a force field that works well for diffusion does not necessarily guarantee accurate adsorption predictions (and vice versa) [184]. In contrast to the monotonically decreasing dihydrogen diffusivities from Salles et al, [182,183] dihydrogen diffusion in a suite of IRMOFs simulated by Yang and Zhong showed that hydrogen diffusivity increased slightly with loading, but then sharply decreased [170].…”
Section: Single Component Diffusion In Rigid Metal-organic Frameworkmentioning
confidence: 86%
“…Figure 7 shows that self-diffusion coefficients calculated with the modified one-site model correlate the best with experimental QENS measurements. This modified force field performed poorly in predicting H 2 adsorption isotherms, cautioning the reader that a force field that works well for diffusion does not necessarily guarantee accurate adsorption predictions (and vice versa) [184]. In contrast to the monotonically decreasing dihydrogen diffusivities from Salles et al, [182,183] dihydrogen diffusion in a suite of IRMOFs simulated by Yang and Zhong showed that hydrogen diffusivity increased slightly with loading, but then sharply decreased [170].…”
Section: Single Component Diffusion In Rigid Metal-organic Frameworkmentioning
confidence: 86%
“…f) The same six interacting malonate groups illustrated in (e) accompanied by their corresponding C60 buckyballs. g) An iRASPA view of the packing and the h) surface occupancy calculated with OLEX2 highlighting the potential cavities surrounding the [60]fullerene in red.…”
Section: Figurementioning
confidence: 99%
“…Some images were created using the iRASPA software. [58] This paper describes objective technical results and analysis. Any subjective views or opinions that might be expressed in the paper do not necessarily represent the views of the U.S. Department of Energy or the United States Government.…”
mentioning
confidence: 99%